1998
DOI: 10.1111/j.1540-4781.1998.tb02595.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of First Language and Phonological Accessibility on Kanji Recognition

Abstract: This study examines the transfer of learners' first language (Ll) orthographic processing strategies to second language (L2) processing. Two groups of college students learning Japanese, a group of learners whose L1 writing system is phonographic and another group whose L1 employs a morphographic writing system, were tested on their ability to represent novel kanji characters in short-term memory. For students in the phonographic language background group, phonologically accessible characters (i.e., characters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
1
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 54 publications
(73 reference statements)
4
34
1
2
Order By: Relevance
“…One would be the use of nonreal words in the measures; a few studies on L1 effects on L2 word recognition use pseudowords and nonwords in their measures (e.g., Koda, 1988Koda, , 1990Mori, 1998). This may be because the research inquiry of the studies prefers nonreal words as stimuli; however, the limitations regarding the usage of pseudowords or nonwords as stimuli have been pointed out.…”
mentioning
confidence: 96%
“…One would be the use of nonreal words in the measures; a few studies on L1 effects on L2 word recognition use pseudowords and nonwords in their measures (e.g., Koda, 1988Koda, , 1990Mori, 1998). This may be because the research inquiry of the studies prefers nonreal words as stimuli; however, the limitations regarding the usage of pseudowords or nonwords as stimuli have been pointed out.…”
mentioning
confidence: 96%
“…Akamatsu, 2003;Chikamatsu, 1996;Koda, 2000Koda, , 2008Mori, 1998;Muljani, Koda, & Moates, 1998). For example, Koda (1989Koda ( , 1990 found that readers with an L1 logographic script learning background are better at L2 reading when deprived of the ability to process words phonologically than readers with an L1 alphabetic script learning background.…”
Section: Processing Differentials Between Logographic and Alphabetic mentioning
confidence: 95%
“…Para Mori (1998), aunque una unidad morfémica está asociada con una forma fonética, el sistema morfográfico dista mucho de ser igual a un sistema fonográfico. Una razón es que no existe una relación uniforme entre grafema y fonema.…”
Section: Antecedentesunclassified
“…De acuerdo con Mori (1998), la investigación en psicología experimental en adquisición del lenguaje y en lingüística ha establecido básicamente que el lector de cualquier lenguaje usa códigos fonológicos para acceder a la memoria de corto plazo que le permite acceder al significado de un texto. No obstante, se reconoce que existen diferencias estructurales entre un sistema fonográfico y morfográfico que podría provocar que lectores habituados a sus respectivos sistemas de escritura usen las mismas estrategias para tratar de interpretar códigos fonológicos en representaciones visuales.…”
Section: Antecedentesunclassified